Sex estimation using angular measurements of nasion, sella, and glabella on lateral cephalogram among Indonesian adults in Yogyakarta - Aini Hasibah Ningtyas; Rini Widyaningrum; Rurie Ratna Shantiningsih; Ryna Dwi Yanuaryska (Egyptian Journal of Forensic Sciences, 2023)
Abstract Background Sex estimation gives the probability that someone is classified as a male or a female. Lateral cephalogram analysis can be used for sex estimation due to the resistance and dimorphism of the skull. Glabella has been known to have dimorphic characteristic in male and female, while nasion and sella have been widely used as a standard point in many craniometric measurements. This study aimed to develop an equation using nasion–sella–glabella (NSG), sella–glabella–nasion (SGN), and glabella–nasion–sella (GNS) angles on lateral cephalograms for sex estimation among Indonesian adults in Yogyakarta, Indonesia. Results A total of 138 adults (aged 20–40 years) digital lateral cephalograms were taken from the dental records at Universitas Gadjah Mada Dental Hospital (108 used to form the equation of sex estimation; 30 used to test the equation), and the parameters were measured with EzDent-i Vatech. An independent t-test was used to analyze the differences in the angles between male and female adults. The equation for sex estimation was determined using discriminant function analysis. The average measurements of the NSG angles in male and female adults were 9.64° ± 1.36° and 11.21° ± 1.57°, respectively, the SGN angles were 54.65° ± 4.19° and 60.83° ± 4.13°, respectively, whereas the GNS angles were 118.33° ± 4.61° and 109.84° ± 5.19°, respectively. The independent t-test revealed a significant difference (p < 0.05) between male and female adults. Discriminant function analysis yielded an equation for sex estimation using the NSG, SGN, and GNS angles with an accuracy of up to 75.9%, with the accuracy of sex estimation based on the testing sample being 70%. Conclusion Based on the findings of this study, male Indonesian adults have a smaller NSG and SGN angles but a bigger GNS angle than female adults. Related to the accuracy, the study’s findings indicate that the discriminant function of NSG, SGN, and GNS angles for sex estimation should not be generalized in wider population. More cephalogram parameters must be investigated in future studies on sex estimation.